Stability of Routine Hematology Sample Using The Medonic M-Series Analyzer - Eva Ayu Maharani; Dewi Astuti (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2020)
Routine hematology tests (Hb, Hct, RBC, WBC, PLT) generally done by automation methods using a hematology analyzer. Ideally, the examinations should be done as soon as possible, although, in some circumstances, it can be delayed. Based on the literature, the sample for routine hematology testing should be processed within 4 – 8 hours of venesection. Some studies revealed that the sample could be stored for up to 48 hours, and it can be influenced by the technology applied to the hematology analyzer. Studies conducted to see the stability of the samples using a hematology analyzer with impedance technology. Tests performed on whole blood samples collected from 12 ostensibly healthy individuals, immediately after collection (fresh sample,